2002
DOI: 10.1074/jbc.m200243200
|View full text |Cite
|
Sign up to set email alerts
|

Elastase-released Epidermal Growth Factor Recruits Epidermal Growth Factor Receptor and Extracellular Signal-regulated Kinases to Down-regulate Tropoelastin mRNA in Lung Fibroblasts

Abstract: Elastase/anti-elastase imbalance is a hallmark of emphysema, a chronic obstructive pulmonary disease associated with the rupture and inefficient repair of interstitial elastin. We report that neutrophil elastase (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 76 publications
3
54
0
Order By: Relevance
“…Several observations were made. 1) We found that, similar to primary neonatal rat lung fibroblasts (5), NE signals to tropoelastin mRNA downregulation in RFL-6 cells via release of EGF-like ligands (found in both type of cells) and TGF-␣-like polypeptides (found only in RFL-6 cells) and subsequently activates the EGFR/MEK/ERK cascade, suggesting that this might be a common response of the various elastogenic cells to elastolytic injury. 2) We demonstrated that the EGFR/MEK/ERK-dependent tropoelastin mRNA downregulation actually translates into major reduction of tropoelastin protein expression and insoluble elastin levels, signifying the overall inhibitory impact of EGFR/MEK/ERK cascade signaling on elastogenesis in lung fibroblasts.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Several observations were made. 1) We found that, similar to primary neonatal rat lung fibroblasts (5), NE signals to tropoelastin mRNA downregulation in RFL-6 cells via release of EGF-like ligands (found in both type of cells) and TGF-␣-like polypeptides (found only in RFL-6 cells) and subsequently activates the EGFR/MEK/ERK cascade, suggesting that this might be a common response of the various elastogenic cells to elastolytic injury. 2) We demonstrated that the EGFR/MEK/ERK-dependent tropoelastin mRNA downregulation actually translates into major reduction of tropoelastin protein expression and insoluble elastin levels, signifying the overall inhibitory impact of EGFR/MEK/ERK cascade signaling on elastogenesis in lung fibroblasts.…”
Section: Discussionmentioning
confidence: 58%
“…Previously, investigators in our group have demonstrated that NE releases biologically active EGFR ligands, such as EGF-like polypeptides, and initiates EGFR-dependent MEK/ ERK activation resulting in downregulation of tropoelastin mRNA levels in neonatal rat lung fibroblasts (5). In the present study we aimed to dissect the mechanism of EGFR/MEK/ ERK-mediated tropoelastin mRNA downregulation, as well as to determine its impact on elastogenesis in lung fibroblasts.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In addition to its described role in tumour cell invasion and metastasis, the serine protease PMN-E may, similar as has been suggested for uPA for human ovarian carcinoma cells (Fischer et al, 1998) and breast cancer cells (Foekens et al, 1995), provoke cell proliferation via enzymatic activation of several growth factor (receptor) pathways. In this respect, the ability of elastase to cleave or activate several growth factors or receptors, such as EGF and EGF receptor (Di Camillo et al, 2002), IL-2 and IL-6 receptor (Bank et al, 1999), stromal cellderived factor-1 (Valenzuela-Fernandez et al, 2002), supports such a local elastase-directed growth interfering mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…QRT-PCR also verified TGF-␤1 and PDGFRA expression, which were detected by SAGE alone (Table 2). Of these eight genes, EGR-1 (24), FOS (25), and TGF-␤1 (26) are well known COPD-responsive genes. To our knowledge, the other genes are not known to be associated with COPD or smoking.…”
Section: Confirmation Of Candidate Genes By Qrt-pcrmentioning
confidence: 99%